1998
DOI: 10.1002/hep.510280104
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic and predictive value of ascites nitric oxide levels in patients with spontaneous bacterial peritonitis

Abstract: Nitric oxide (NO) is a messenger molecule involved in pathogen suppression. Cirrhosis is characterized by an increased risk for infections, including spontaneous bacterial peritonitis (SBP). The role of NO in the infections that develop in cirrhosis has not been clearly established. The aim of this study was to investigate the utility of measuring ascites NO in the diagnosis of SBP and/or in determining the predisposition of cirrhotic patients to develop this infection. Nitric oxide metabolites (nitrites ؉ nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 18 publications
(24 reference statements)
1
13
1
Order By: Relevance
“…Previous studies in patients with SBP treated with antibiotics alone have demonstrated an intense and progressive increase in the serum levels of NOx which persists for several weeks after resolution of the infection [16]. This feature was not observed neither in our study nor in a previous investigation [17].…”
Section: Discussioncontrasting
confidence: 81%
“…Previous studies in patients with SBP treated with antibiotics alone have demonstrated an intense and progressive increase in the serum levels of NOx which persists for several weeks after resolution of the infection [16]. This feature was not observed neither in our study nor in a previous investigation [17].…”
Section: Discussioncontrasting
confidence: 81%
“…Pro-inflammatory cytokines induce an endothelial activation, which can be detected by increased synthesis of nitric oxide [29] or by expression of adhesion molecules on the cellular surface [9Á/11], and they have been implicated in hemodynamic changes present in cirrhotic patients [30,31]. Ele- vated values of soluble adhesion molecules were detected in the early stages of liver dysfunction: plasma concentrations were increased in patients in Child Pugh class A, with higher values found in those in class B or C. Serum concentrations of endothelial adhesion molecules ICAM-1 and VCAM-1 were correlated with blood pressure values.…”
Section: Discussionmentioning
confidence: 99%
“…105 However, low ascites NO levels, although predictive of a poor prognosis, are unable to predict SBP in patients with cirrhosis. 106 NO also participates in maintaining gut barrier function. 107 It increases gastrointestinal mucus secretion, modulates epithelial chloride transport and associated fluid secretion, maintains blood flow, inhibits intestinal muscular motor activity, reduces mast cell reactivity and mediator release, suppresses neutrophil aggregation and sequestration, and scavenges reactive oxygen metabolites.…”
Section: Role Of Nitric Oxidementioning
confidence: 99%